Respuesta :
If you would like to simplify 5 + 2{x - 4[3x + 7(2 - x)]}, you can do this using the following steps:
5 + 2{x - 4[3x + 7(2 - x)]} = 5 + 2{x - 4[3x + 7 * 2 - 7x]} = 5 + 2{x - 4[-4x + 14]} = 5 + 2{x - 4 * (-4)x + (-4) * 14} = 5 + 2{x + 16x - 56} = 5 + 2x + 2 * 16x - 56 * 2 = 5 + 2x + 32x - 112 = 34x - 107
The correct result would be 34x - 107.
5 + 2{x - 4[3x + 7(2 - x)]} = 5 + 2{x - 4[3x + 7 * 2 - 7x]} = 5 + 2{x - 4[-4x + 14]} = 5 + 2{x - 4 * (-4)x + (-4) * 14} = 5 + 2{x + 16x - 56} = 5 + 2x + 2 * 16x - 56 * 2 = 5 + 2x + 32x - 112 = 34x - 107
The correct result would be 34x - 107.
Answer:
Option (b) is correct
The simplified form of given expression [tex]5+2\{x-4[3x+7(2-x)]\}[/tex] is 34x - 107.
Step-by-step explanation:
Given expression [tex]5+2\{x-4[3x+7(2-x)]\}[/tex]
We have to evaluate the value of given expression
Consider the given expression [tex]5+2\{x-4[3x+7(2-x)]\}[/tex]
Apply PEDMAS rules,
Where P denoted parenthesis
E denotes exponents,
M denotes multiplication,
D denotes division,
A denotes addition,
S denotes subtraction.
[tex]\Rightarrow 5+2\{x-4[3x+14-7x)]\}[/tex]
Solving further, we have,
[tex]\Rightarrow 5+2\{x-12x-56+28x\}[/tex]
Solving further, we have,
[tex]\Rightarrow 5+2x-24x-112+56x[/tex]
Simplify, we get,
[tex]\Rightarrow 34x-107[/tex]
Thus, the simplified form of given expression [tex]5+2\{x-4[3x+7(2-x)]\}[/tex] is 34x - 107.